Engaging with uncertainty: Information practices in the context of disease surveillance in Burkina Faso. Issue 3 (September 2021) - Rasmussen, Stine Loft; Sahay, Sundeep
Abstract: Uncertainty is inherent to outbreaks of infectious diseases; a topic of global concern. Addressing global outbreaks requires – among other things – well-functioning systems to produce information. The aim of the paper is to understand uncertainty in the context of information systems (IS) and to analyze the role of formal and informal information practices in identifying and responding to communicable diseases in the context of developing countries. Our empirical focus is on a dengue outbreak in 2016 in Burkina Faso- Dengue was then unknown in the context and formal "techne" based information systems were inadequate in dealing with it. Drawing on work defining uncertainty as a resource, we extend our practice-based theoretical lens with the concepts of "general and specific metis" to describe practices neither established formally or informally, but which evolve as the disease unfolds. While general metis represents practices based on the broader understanding of the context which the health staff have, specific metis relates to the particular practices they construct to acquire, share, and react on information as the disease unfolds. Our paper contributes primarily in foregrounding the role of uncertainty in information systems research and how this relates to formal, informal and emerging information practices. Highlights: Uncertainty is an aspect of decision making, which tends to be ignored or omitted in HIS and IS research. Health information systems are designed assuming information is available for action. In Burkina Faso conditions of uncertainty are inherent to disease surveillance and response. Health workers improvise response even with no or limited information at hand. Health information systems could be improved by adapting to the uncertainties occurring in practice.